CHOICE OF OPTIMAL CONSTRUCTIVE AND TECHNOLOGICAL PARAMETERS OF FLAME FURNACES OF CHAMBER TYPE WITH HIGH-SPEED BURNERS WITH THE PURPOSE OF PROVIDING HEATING UNIFORMITY - I. A. Trusova; P. E. Ratnikov; D. V. Mendelev; S. V. Korneev (Литьë и металлургия)
It is shown that at carrying out of multi-variant calculations the possibility to achieve uniformity of convection heating by means of variation of constructive parameters of working furnace chamber including burners location, and in such a way to intensify the heating of metal.